The combination of Mycobacterium tuberculosis fusion proteins LT33 and LT28 induced strong protective immunity in mice - He, Pu; Wang, Juan; Tan, Daquan; Hu, Lina; Ma, Yanlin; Mi, Youjun; Li, Fei; Zhang, Tingting; Du, Yunjie; Zhang, Wenhua; Li, Jixi; Jiao, Lei; et al. (Frontiers in Immunology, 2024)
Effective subunit vaccines for tuberculosis (TB) must target antigenic components at various stages of infection. In this study, we constructed fusion proteins using secreted antigens from Mycobacterium tuberculosis (M. tuberculosis), specifically ESAT6, CFP10, MPT64, and Rv2645 from the proliferation stage, along with latency-associated antigens Rv1738 and Rv1978. The resulting fusion proteins, designated LT33 (ESAT6-CFP10-Rv1738) and LT28 (MPT6461-170-Rv19788-60-Rv264521-80), were combined with an adjuvant containing dimethyldioctadecylammonium bromide (DDA), polyriboinosinic polyribocytidylic acid (PolyI:C), and cholesterol to construct subunit vaccines. We evaluated the subunit vaccine effect in C57BL/6 mice and revealed that LT33 and LT28 exhibited strong immunogenicity and induced protective efficacy against aerosol challenge with M. tuberculosis H37Rv. Notably, the combination of LT33 and LT28 led to a significant reduction of 0.77 log10 colony-forming units (CFU) of H37Rv in the lungs compared to the adjuvant control group, highlighting their potential as promising candidates for subunit vaccine against M. tuberculosis infection.